2005
DOI: 10.1038/sj.gt.3302651
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Progress and Prospects: In tissue engineering

Abstract: Tissue engineering (TE) has existed for several years as an area spanning many disciplines, including medicine and engineering. The use of stem cells as a biological basis for TE coupled with advances in materials science has opened up an entirely new chapter in medicine and holds the promise of major contributions to the repair, replacement and regeneration of damaged tissues and organs. In this article, we review the spectrum of stem cells and scaffolds being investigated for their potential applications in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Current research on the 3D culture system is more vital and promising than ever. [44][45][46][47] The utility of 3D systems is underscored by their potential use in drug delivery, study of metastasis, and tissue engineering for therapeutic purposes. The advantage of the 3D cell culture system is its defined geometry that makes it possible to directly relate structure to function and that approximates an in vivo state more closely by allowing spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Current research on the 3D culture system is more vital and promising than ever. [44][45][46][47] The utility of 3D systems is underscored by their potential use in drug delivery, study of metastasis, and tissue engineering for therapeutic purposes. The advantage of the 3D cell culture system is its defined geometry that makes it possible to directly relate structure to function and that approximates an in vivo state more closely by allowing spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [10] reported that macrophages in which the NF-ÄžB pathway was inhibited by transduction with dominant-negative IÄžB developed anti-inflammatory properties and reduced glomerular injury in nephrotoxic serum nephritis. Despite genetic manipulation of macrophages being applied successfully in experimental models of renal disease, major obstacles to clinical application of this technology include the danger of viral vectors and difficulty of controlling levels of gene expression in vivo [11]. Macrophages modified ex vivo with IFN-Îł into M1 and infused into leucopenic rats substantially augmented renal injury, an effect which could be blocked with glucocorticoids [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy has shown promising results in the field of tissue engineering [33,34]. It could potentially utilize biological principles to guide cellular behaviors into scaffolds.…”
Section: In Situ Transfection Of Multilayers On the Poly(lactic Acid)mentioning
confidence: 99%